Molecular Insights into Viral Pathogenesis: Statistical Analysis of Host Response and Gene Expression Dynamics Across Infection Severity Levels - Al-Hayani, Noor Naji; M. Saeed, Ruya Abdulhadi (American Journal of Biology and Natural Sciences, 2025)
Understanding the molecular mechanisms underpinning viral infections remains pivotal in developing targeted therapeutic interventions. This study investigates the association between infection severity and key host biological responses, specifically focusing on host response levels and gene expression dynamics in viral infections. Using a structured dataset comprising control and infected groups across various infection severity scores, descriptive and inferential statistical analyses were employed to decipher patterns in immune activation and transcriptional changes. While descriptive statistics suggested subtle variations in host response and gene expression across groups, One-Way ANOVA (Welch's) indicated no statistically significant differences (p ≤ 0.05) among infection severity levels. The observed variability highlights complex host-pathogen interactions, possibly influenced by additional molecular or environmental factors beyond severity scoring alone. These findings underscore the necessity for expanded datasets, incorporation of additional biomarkers, and refined analytical frameworks to unravel the nuanced pathways of viral pathogenesis.